A Quantum Approach in LiFi Security using Quantum Key Distribution - Vinoth Kumar V, Karthikeyan T, Praveen Sundar P V, Magesh G, Balajee J.M (International Journal of Advanced Science and Technology, 2020)
Light Fidelity (LiFi) can be employed to design a wireless system of networks forcommunication. Current technology, which is Wi-Fi based has some drawbacks that includesspeed and bandwidth limit, which results in making the network less reliable compared to LiFi.The LiFi has more advantage over Wi-Fi but in this LiFi oriented networks, the area of securityis not researched so seriously till now, therefore this paper discuss about the LiFi basedcommunication and how to secure the communication using several cryptography schemes, withthis paper we also present a survey on some applications of LiFi. So, for choosing the bestpossible security, the survey on the comparison among various classical cryptographic methodslike RSA, Caesar cipher or the quantum crypto methods like BB84 or B92 algorithm is also done.Since we are trading with communication through light then what could the best way to securingthis communication than Quantum Cryptography that is why this paper mainly focused on whichis the best algorithm can be utilized to provide the key sharing using the Quantum keydistribution method and what type of security each protocol provides to the communicatingparties